Responsiveness of children with celiac disease to different hepatitis B vaccination protocols - Necati BALAMTEKİN and Nuray USLU and Gökhan BAYSOY and İnci SALTIK-TEMİZEL and Hülya DEMİR and; l YÜCE (Turkish Journal of Gastroenterology, 2019)
-